(untitled) (The Macau Ricci Institute Journal, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritualtheological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.